Ground improvement method using rubber shredded and acrylonitrile butadiene styrene - Aziz, Fatin Nur Ayuni Abd (Universiti Sains Malaysia, 2017)
Malaysian citizen are increasing rapidly year by year. As the population growth, land use will increase significantly and there will be more civil engineering project will be carried on soft soil. Soft soil needs ground improvement method in order to stabilize the soil and prevent uneven settlement. As the solution, geotextiles are used to improve stability of the soil and reduce cost of constructing earthwork over such soils. Method used for this research was rubber shredded and acrylonitrile butadiene styrene that mixed with soil in order to stabilize the soil. This research was to investigate suitability uses of rubber shredded and acrylonitrile butadiene styrene as an additive to clay and laterite. This research also investigates strength of the soil with and without additive using triaxial test under consolidated undrained.